Pengaruh Media Pembelajaran Baamboozle Terhadap Minat Belajar Matematika Siswa Pada Sanggar Bimbingan Aisyiyah Pandan Malaysia - Khoiroh, Nur; Sari, Suci Perwita (Jurnal Gentala Pendidikan Dasar, 2025)
Success in school is mainly determined by a student's interest in studying, particularly when it comes to mathematics, which many children find challenging. The purpose of this study is to determine the effect of the Baamboozle learning media on students' interest in learning mathematics at Sanggar Bimbingan Aisyiyah Pandan Malaysia. The research used a one-group pretest-posttest design and a pre-experimental methodology. Seven fifth -grade children were among the participants. A learning interest questionnaire was used to collect the data, and SPSS version 27's paired sample t-test was used for analysis. The research results showed that the average pretest score was 39,43, while the average posttest score increased to 66,57. The Paired Sample T-Test yielded a significance value of 0.001, which is smaller than 0.05 (0.001 < 0.05). Thus, it has been proven that the use of Baamboozle learning media has a significant influence on students' interest in learning mathematics at Sanggar Bimbingan Aisyiyah Pandan Malaysia.